2009
DOI: 10.1063/1.3052074
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the water/corundum (0001) interface

Abstract: For the reliable long-term modeling of the actinide migration in geological formations, the adsorption/desorption properties and the reactivity of mineral surfaces must be understood at the molecular level. The adsorption of radioisotopes at mineral surfaces of the aquifer is an important process that leads to the retention of contaminants such as radionuclides. Their transport by the ground water is either retarded or even completely inhibited by the presence of such a surface. Accordingly, this subject is of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 61 publications
3
34
0
Order By: Relevance
“…We employed the same methodology as in our recent theoretical paper [6], where we showed that the RI-DFT method [15][16][17][18][19][20] as implemented in the TURBOMOLE program package [16][17][18][19][21][22][23] provides very accurate results for this class of systems. It turned out, that the BP86 functional [10][11][12][13][14] together with the cc-pVDZ basis set [24] is the optimal combination of functional and basis set for our purpose [6].…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We employed the same methodology as in our recent theoretical paper [6], where we showed that the RI-DFT method [15][16][17][18][19][20] as implemented in the TURBOMOLE program package [16][17][18][19][21][22][23] provides very accurate results for this class of systems. It turned out, that the BP86 functional [10][11][12][13][14] together with the cc-pVDZ basis set [24] is the optimal combination of functional and basis set for our purpose [6].…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…[6] and references therein and for the interaction of uranyl see [7][8][9], but to best of our knowledge there are no theoretical calculations dealing with the sorption of trivalent actinide/lanthanide ions on mineral surfaces.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Nevertheless, these methods significantly contributed to the interpretation of the spectroscopic measurements and to the understanding the mechanism of the cooperativity of the hydrogen bonding. [21][22][23][24] The classia) Email: janecek_jiri@centrum.cz b) Email: patrice.paricaud@ensta-paristech.fr cal atomistic simulations can treat much larger systems (compared to quantum methods) and thus they represent important tool to study the internal structure of associating systems. Several recent as well as classical studies were aimed to analyze the size and topology of associated species.…”
Section: Introductionmentioning
confidence: 99%